Geneza i rozwój rankingów uczelni wyższych - Gromkowska-Melosik , Agnieszka (Studia Edukacyjne, 2021)
The Author of the article reconstructs the origin and development of rankings of higher education institutions. In the first part the current ranking are listed and the importance of rankings for universities is stressed. Next, the beginning of American rankings in the XIXth century is presented as well ad turning points in methodologies of evaluation. The rankings created by Charles Babcock and James McKeena Cattell in the first decades of XXth century are analysed. The special attention is paid to changes in criteria used to assess the educational institutions in subsequent decades. In conlusive part the Author criticizes rankings for one-dimensional and reductionist approach to academic world.